Influence of oxytocin administration on somatosensory evoked magnetic fields induced by median nerve stimulation during hand action observation in healthy male volunteers - Ono, Yasuki; Hirosawa, Tetsu; Hasegawa, Chiaki; Ikeda, Takashi; Kudo, Kiwamu; Naito, Nobushige; Yoshimura, Yuko; Kikuchi, Mitsuru (PloS one, 2021)
Watching another person’s hand movement modulates somatosensory evoked magnetic fields (SEFs). Assuming that the mirror neuron system may have a role in this phenomenon, oxytocin should enhance these effects. This single-blinded, placebo-controlled, crossover study therefore used magnetoencephalography (MEG) to investigate SEFs following electrical stimulation of the right median nerve in 20 healthy male participants during hand movement observation, which were initially presented as static images followed by moving images. The participants were randomly assigned to receive either oxytocin or saline during the first trial, with the treatment being reversed during a second trial. Log-transformed ratios of the N20 and N30 amplitudes were calculated and compared between moving and static images observations. Phase locking (calculated using intertrial phase coherence) of brain oscillations was also analyzed to evaluate alpha, beta and gamma rhythm changes after oxytocin administration. Log N30 ratios showed no significant changes after placebo administration but showed a decreasing tendency (albeit not significant) after placebo administration, which may suggest mirror neuron system involvement. In contrast, log N20 ratios were increased after placebo administration, but showed no significant change after oxytocin administration. Interestingly, the gamma band activity around N20 increased after placebo administration, suggesting that oxytocin exerted an analgesic effect on median nerve stimulation, and inhibited the gamma band increase. Oxytocin might therefore modulate not only the mirror neuron system, but also the sensory processing associated with median nerve stimulation.